Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

A method to quantify infection and colonization of holm oak (Quercus ilex) roots by Phytophthora cinnamomi. - Ruiz-Gómez, Francisco J; Sánchez-Cuesta, Rafael; Navarro-cerrillo, Rafael M; Pérez-de-Luque, Alejandro (Plant methods, 2012)
ABSTRACT: Phytophthora cinnamomi Rands. is an important root rot pathogen widely distributed in the north hemisphere, with a large host range. Among others diseases, it is known to be a principal factor in the decline of holm oak and cork oak, the most important tree species in the "dehesa" ecosystem of south-western Spain. Previously, the focus of studies on P. cinnamomi and holm oak have been on molecular tools for identification, functional responses of the host, together with other physiological and morphological host variables. However, a microscopic index to describe the degree of infection and colonization in the plant tissues has not yet been developed. A colonization or infection index would be a useful tool for studies that examine differences between individuals subjected to different treatments or to individuals belonging to different breeding accessions, together with their specific responses to the pathogen. This work presents a methodology based on the capture and digital treatment of microscopic images, using simple and accessible software, together with a range of variables that quantify the infection and colonization process.
Keywords: histology; Holm oak decline; infection degree; Microscopy; Phytophthora; root rot